The PARC Lesion: A Proximal Avulsion of the Radiocarpal Capsule - Bonte, Francis; Mathoulin, Christophe L. (Journal of Wrist Surgery, 2017)
Purpose A proximal avulsion of the radiocarpal capsule (PARC) is a cause of persisting posttraumatic wrist pain. This lesion is often overlooked and left untreated during wrist arthroscopy.Materials and Methods A record review was performed on 13 patients with this lesion who underwent diagnostic wrist arthroscopy after failed conservative treatment. We retrospectively reviewed the results of an arthroscopic repair method in 13 patients.Results In 11 of the 13 consecutive cases the lesion was sutured using an arthroscopic dorsal capsule-ligamentous repair technique. Postoperatively, all high-demand patients were able to return to their previous sports.Discussion The PARC lesion is usually overlooked during diagnostic arthroscopy since it may be covered by synovial or fibrous tissue. It often coexists with scapholunate ligament or triangular fibrocartilage complex injuries. This lesion is amenable to an arthroscopic repair with satisfactory clinical results.
Keywords: PARC lesion; wrist arthroscopy; radiocarpal; capsular tear